2022
DOI: 10.1093/ntr/ntac201
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Status, Nicotine Medication, Vaccination, and COVID-19 Hospital Outcomes: Findings from the COVID EHR Cohort at the University of Wisconsin (CEC-UW) Study

Abstract: Introduction Available evidence is mixed concerning associations between smoking status and COVID-19 clinical outcomes. Effects of nicotine replacement therapy (NRT) and vaccination status on COVID-19 outcomes in smokers are unknown. Methods Electronic health record data from 104 590 COVID-19 patients hospitalized February 1, 2020 to September 30, 2021 in 21 U.S. health systems were analyzed to assess associations of smoking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…However, the frequency and duration of smoking, or time since quitting tobacco use also influence the increased risk posed by this habit. The long-term damaging effects of smoking have been studied by comparing never-smokers to former [ 204 , 789 , 790 , 791 , 792 ] or ever-smokers (former and current smokers combined) [ 124 , 204 , 793 , 794 , 795 ], which consistently showed more severe outcomes (e.g., hospitalization, ICU admission, MV and death) in the latter groups. However, although current smokers compared to (current) non-smokers seem to be more prone to experience severe symptoms and death [ 123 , 794 , 796 , 797 ], when comparing current smokers to never-smokers, some publications reported increased severity [ 204 , 788 , 796 , 798 ], while others no effect [ 791 , 792 , 799 ], and surprisingly, recent cohort studies found lower rates of severe outcomes [ 789 , 790 ] in the smoker group of the study.…”
Section: Host Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the frequency and duration of smoking, or time since quitting tobacco use also influence the increased risk posed by this habit. The long-term damaging effects of smoking have been studied by comparing never-smokers to former [ 204 , 789 , 790 , 791 , 792 ] or ever-smokers (former and current smokers combined) [ 124 , 204 , 793 , 794 , 795 ], which consistently showed more severe outcomes (e.g., hospitalization, ICU admission, MV and death) in the latter groups. However, although current smokers compared to (current) non-smokers seem to be more prone to experience severe symptoms and death [ 123 , 794 , 796 , 797 ], when comparing current smokers to never-smokers, some publications reported increased severity [ 204 , 788 , 796 , 798 ], while others no effect [ 791 , 792 , 799 ], and surprisingly, recent cohort studies found lower rates of severe outcomes [ 789 , 790 ] in the smoker group of the study.…”
Section: Host Factorsmentioning
confidence: 99%
“…The long-term damaging effects of smoking have been studied by comparing never-smokers to former [ 204 , 789 , 790 , 791 , 792 ] or ever-smokers (former and current smokers combined) [ 124 , 204 , 793 , 794 , 795 ], which consistently showed more severe outcomes (e.g., hospitalization, ICU admission, MV and death) in the latter groups. However, although current smokers compared to (current) non-smokers seem to be more prone to experience severe symptoms and death [ 123 , 794 , 796 , 797 ], when comparing current smokers to never-smokers, some publications reported increased severity [ 204 , 788 , 796 , 798 ], while others no effect [ 791 , 792 , 799 ], and surprisingly, recent cohort studies found lower rates of severe outcomes [ 789 , 790 ] in the smoker group of the study. The short-term effects of tobacco use are harder to measure in clinical settings, but ambiguous results on the effect of current smoking behavior on COVID-19 might imply further physiological and immunological effects that differ from the mechanisms responsible for long-lasting damage in the lungs.…”
Section: Host Factorsmentioning
confidence: 99%
“…Time period of admission was a two‐level variable coded as before COVID‐19 vaccine availability (February 1, 2020 to December 10, 2020) or after vaccine availability (December 11, 2020 to November 30, 2021). In addition, vaccination status before the index admission was analyzed as a three‐level variable (0, 1, or 2 or more doses) 13,24 . Supplementary Text describes the manufacturer of up to the first three doses of vaccination received before the index admission.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, vaccination status before the index admission was analyzed as a three-level variable (0, 1, or 2 or more doses). 13,24 Supplementary Text S2 describes 17,27 Previous research established threshold effects of area deprivation on hospital readmission as greater than or equal to the 80th percentile. 19 Area SDI was dichotomized into low (below the 80th percentile) and high (greater than or equal to the 80th percentile).…”
Section: Predictorsmentioning
confidence: 99%
“…only used smokeless tobacco. In 2021,13.5% of US adults (estimated 34.1 million) reported having COVID-19 (Table 3), 60.8% (153.9 million) ever tested for COVID-19, 12.5% (31.7 million) ever tested positive for COVID-19, 54.8% (19.6 million) had medium or severe symptoms (vs. no/mild symptoms) associated with COVID-19. Among symptomatic adults, 60.5% (21.5 million) and 58.2% (20.7 EBRAHIMI KALAN ET AL.| 3 of 10 T A B L E 1 T A B L E 1 (Continued) Abbreviations: CI, confidence interval; COVID-19, coronavirus disease 2019; NH, Non-Hispanic; NHIS, National Health Interview Survey.…”
mentioning
confidence: 99%